Methods of Resolving Problems Connected with Raising Competitiveness of Mobile Application - I. P. Lebedeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Problems that should be resolved by marketer when a new mobile application is put on sale can be divided into two groups. The 1-st one is connected with customer attraction, the 2-nd one – with his/her retaining. On the one hand, resolving these problems is directly connected with advertizing campaign and marketing research, however the majority of companies – developers of mobile applications have no financial possibilities for marketing accompaniment of application entering market. The article studies research, which can be done by own forces. With adequate analysis they can lead to high-quality results and increase in the number of users. Apart from that the author proposes the method of analyzing event arrangement in application software section, which can help keep an eye on user’s steps and interpret them to find key problems of the application. This method of event arrangement is not new for developers and it is offered by existing analytical platforms, however interpretation of obtained results and subsequent company steps can become a serious task. Further development of such methodology based on analytics, segmentation and reviews of users could resolve a problem of developing by companies-developers of mobile applications their own marketing strategy verified in practice.